MODEL PEMBELAJARAN SURVEY, QUESTION, READ, RECITE, REVIEW, REFLECT (SQ4R) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA - Aulia, Indah (Epsilon: Jurnal Pendidikan Matematika, 2021)
Abstract: The problem in this study is that the mathematical problem solving ability of class X SMA Negeri 1 Gedung Tataan has not been maximized. The SQ4R model as an alternative solution is used, therefore the purpose of this study is to determine the effect of the Survey, Question, Read, Recite, Review, Reflect (SQ4R) model on the mathematical problem solving abilities of X grade students of SMA Negeri 1 Gedung Tataan. This study uses a quasi-experimental method, as well as data analysis using parametric statistics. The population in this study were all students of Class X SMA Negeri 1 Gedung Tataan which consisted of 10 classes, while the sample was taken 2 classes, namely Class X-2 as the experimental class and Class X-3 as the control class. The sample was taken using the Cluster Random Sampling technique. To find out the students' mathematical problem solving ability, it is measured by a test in the form of an essay with 5 questions. From the results of hypothesis testing using the statistical formula t-test, the value of t = 6.14 is obtained. From the t distribution table at a significant level of 5%, it is known that t = t_((1-Î±)) = 2.00, which means that t > t is 6.14 > 2.00, so it can be concluded that "There is an effect of the Survey model, Question , Read, Recite, Review, Reflect (SQ4R) on the mathematical problem solving abilities of Class X students in the even semester of SMA Negeri 1 Gedung Tataanâ€. This situation can also be seen from the average value of students' mathematical problem solving abilities where the experimental class has an average value of 78.63 and the control class has an average value of 55.5.